Approximately Informed, Occasionally Monitorial? Reconsidering Normative Citizen Ideals. (April 2018) - Ytre-Arne, Brita; Moe, Hallvard
This article identifies gaps between normative ideals and realistic accounts of news use in democracy today. Starting from the widespread but unrealistic ideal of the informed citizen, and its more realistic development through notions of the monitorial citizen, we analyze comprehensive qualitative data on news users' experiences. We describe these news users as approximately informed, occasionally monitorial. This description emphasizes the limited, shifting, and partial figurations of societal information that citizens are able to obtain through their use of journalistic and social media, and thereby challenges normative ideals. How do monitorial ideals function when the citizens are only occasionally on guard? By zooming in on three key gaps between even a less demanding ideal and actual practices in news use, we underline the need to further reconceptualize our expectations of citizens' news use.